Line 35: | Line 35: | ||

<h3> Theorem 3 </h3> | <h3> Theorem 3 </h3> | ||

− | <p> If <i>A</i> is a nonsingular matrix, then <i>A</i><sup>-1</sup> is nonsingular and (<i>A</i><sup>-1</sup>)<sup>-1</sup> = <i>A</i>. | + | <p> If <i>A</i> is a nonsingular matrix, then <i>A</i><sup>-1</sup> is nonsingular and (<i>A</i><sup>-1</sup>)<sup>-1</sup> = <i>A</i>. </p> |

+ | <h3> Theorem 4 </h3> | ||

+ | <p> If A is a nonsingular matrix, then <i>A</i><sup>T</sup> is nonsingular and (<i>A</i><sup>-1</sup>)<sup>T</sup> = (<i>A</i><sup>T</sup>)<sup>-1</sup>. | ||

## Revision as of 07:08, 10 December 2012

## Contents

# Inverse of a Matrix

An *n* x *n* matrix *A* is said to have an inverse provided there exists an *n* x *n* matrix *B* such that *AB* = *BA* = *I*_{n}. We call *B* the inverse of *A* and denote it as *A*^{-1}. Thus, *A**A*^{-1} = *A*^{-1}*A* = *I*_{n}. In this case, A is also called nonsingular.

Example.

A = $ \left(\begin{array}{cccc}4&3\\3&2\end{array}\right) $

A^{-1} = $ \left(\begin{array}{cccc}-2&3\\3&-4\end{array}\right) $

AA^{-1} = $ \left(\begin{array}{cccc}4&3\\3&2\end{array}\right) $$ \left(\begin{array}{cccc}-2&3\\3&-4\end{array}\right) = $ $ \left(\begin{array}{cccc}1&0\\0&1\end{array}\right) $

and A^{-1}A = $ \left(\begin{array}{cccc}-2&3\\3&-4\end{array}\right) $$ \left(\begin{array}{cccc}4&3\\3&2\end{array}\right) = $$ \left(\begin{array}{cccc}1&0\\0&1\end{array}\right) $

### Theorem 1

The inverse of a matrix, if it exists, is unique

### Theorem 2

If *A* and *B* are both nonsingular *n* x *n* matrices (i.e. invertible), then *AB* is nonsingular and (*AB*^{)-1} = *B*^{-1}*A*^{-1}.

### Corollary 1

If *A*_{1}, *A*_{2}, ..., *A*_{r} are *n* x *n* nonsingular matrices, then *A*_{1}*A*_{2}...*A*_{r} is nonsingular an (*A*_{1}*A*_{2}...*A*_{r})^{-1} = *A*_{r}^{-1}*A*_{r-1}^{-1}...*A*_{1}^{-1}.

### Theorem 3

If *A* is a nonsingular matrix, then *A*^{-1} is nonsingular and (*A*^{-1})^{-1} = *A*.

### Theorem 4

If A is a nonsingular matrix, then *A*^{T} is nonsingular and (*A*^{-1})^{T} = (*A*^{T})^{-1}.